Teaching Experience, Organizational Work Climate, and Achievement Motivation as Predictors of Elementary School Teacher Performance - Setyarini Setyarini (Piramida Akademi, 2025)
The purpose of the study was to determine: (1) jointly the contribution of teaching experience, organizational work climate, and achievement motivation, (2) contribution to teaching experience, (3) contribution to the organization's work climate, (4) contribution to achievement motivation towards elementary school. This type of research is quantitative research. Research variables are teaching experience, organizational work climate, achievement motivation and teacher performance. The study population of all elementary school teachers in Lendah Subdistrict in 2018 was 210 teachers. The technique of retrieving data uses a questionnaire. Testing instruments with validity test and reliability test. The analysis used is multiple linear regression analysis. The results of the study: (1) The teaching experience, organizational work climate, and achievement motivation together have a positive and significant contribution to the performance of elementary school teachers. The higher teaching experience, organizational work climate and achievement motivation, teacher performance tends to be high, (2) teaching experience contributes positively to the performance of elementary school teachers. The higher the teaching experience, the teacher's performance tends to be high, (3) The organizational work climate contributes positively to the performance of elementary school teachers. The higher the organization's work climate, the teacher's performance tends to be high, (4) Motivation for achievement positively contributes to the performance of elementary school teachers. These findings imply that school principals and basic education policymakers need to design professional development programs, create a supportive organizational climate, and strengthen achievement motivation as strategic efforts to improve elementary school teacher performance.